2002
DOI: 10.1002/ijc.10530
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of allelic imbalance profiles in synchronous and metachronous bilateral breast carcinomas

Abstract: Bilateral breast cancer (biBC) is a common form of breast cancer; however, it has not been subjected to systematic comparative genetic studies. We allelotyped 28 biBCs on 14 chromosomal arms, addressing 2 lines of questions: (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 16 publications
2
66
0
2
Order By: Relevance
“…See Table 1 for case numbers and a detailed description of the genomic imbalances. supporting the conclusion that most patients with bilateral breast carcinomas have two different diseases (Dawson et al, 1991;Sterns and Fletcher, 1991;Pandis et al, 1995;Shibata et al, 1996;Imyanitov et al, 2002). This notwithstanding, one of the patients presented two bilateral lobular carcinomas sharing all five genomic imbalances by CGH, strongly arguing that one tumour must have metastasised to the contralateral breast, as we have also seen occasionally before (Pandis et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…See Table 1 for case numbers and a detailed description of the genomic imbalances. supporting the conclusion that most patients with bilateral breast carcinomas have two different diseases (Dawson et al, 1991;Sterns and Fletcher, 1991;Pandis et al, 1995;Shibata et al, 1996;Imyanitov et al, 2002). This notwithstanding, one of the patients presented two bilateral lobular carcinomas sharing all five genomic imbalances by CGH, strongly arguing that one tumour must have metastasised to the contralateral breast, as we have also seen occasionally before (Pandis et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Among the principles used have been X-inactivation analysis (Noguchi et al, 1994a, b;Shibata et al, 1996), comparisons of allelic imbalance patterns (Tsuda and Hirohashi, 1995;Imyanitov et al, 2002), or the distribution of TP53 point mutations (Ackerman et al, 1995;Kinoshita et al, 1995;Shibata et al, 1996), but these studies depend heavily on statistical group comparisons and therefore are of limited value in individual patients. We have in the past successfully assessed the pathogenetic and clonal relationships among multiple breast tumours by means of chromosome banding analysis with karyotyping (Pandis et al, 1995;Teixeira et al, 1994Teixeira et al, , 1997.…”
mentioning
confidence: 99%
“…Janschek et al investigated TP53 mutations across 33 patients, but were due to the singlegene assay and lack of normal tissue, only able to determine the clonal status for 13 patients, of which two were determined to have a metastasis rather than a second primary. Imyanitov et al determined status for all but one of 28 investigated cases, using 14 fixed markers for each tumor [5], showing a higher similarity between synchronous CBC than metachronous CBC. Two studies have used CGH to investigate the relationship between the tumors, showing that investigation of genomic imbalances can be used to detect recurrent breast tumors in both the ipsilateral and contralateral settings [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Women with breast cancer have, 20 years after their initial diagnosis, 10-15% cumulative incidence of second primary breast cancer in the opposite breast; contralateral breast cancer (CBC) [4,5]. We and others have previously shown that women with CBC have significantly worse prognosis compared to women with unilateral cancer [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…First, in accordance with other studies, bilateral breast carcinomas are genetically unrelated. [2][3][4] Second, like in unilateral invasive and noninvasive breast carcinomas, LR of breast carcinoma is most likely related to the preceding carcinoma of the ipsilateral breast and not a de novo occurring carcinoma. 22,24 Third, like in unilateral breast carcinomas, LR in bilateral carcinomas is also characterized by an increase of genetic alterations.…”
Section: Discussionmentioning
confidence: 99%